The development of a recombinant hepatitis E vaccine HEV 239 - Li, Shao-Wei (Hum Vaccin Immunother, 2015)
Hepatitis E virus (HEV) infection is one of the main causes of acute hepatitis worldwide. A recombinant hepatitis E vaccine, HEV 239, has been licensed in China for immunizing adults of 16 y old and above. The vaccine antigen contains pORF2 aa 368 - 606 of the HEV genotype 1 expressed in E. coli. The quality of the vaccine is controlled through a combination of biophysical, biochemical and immunochemical methods. The vaccine is well tolerated in adults. The efficacy of the HEV 239 vaccine against symptomatic and asymptomatic infection had been proven to be high during a Phase III clinical trial and long-term follow up. The safety and efficacy of HEV 239 vaccine in certain high-risk populations remains to be further investigated.